Synthesis and kinetic study of rhodium(I) complexes containing substituted cupferrate ligands - Fessha, Fanuel Gebremichael (University of the Free State, 2005)
A number of dicarbonylrhodium complexes of the type [Rh(CH3cupf)(CO)2] as well as their substituted monocarbonyl products [Rh(CH3cupf)(CO)(PX3)] (where X = Ph, p-MeOph, p-Tol, o- Tol and Cy) have been prepared and identified by IR and NMR techniques. The square planar substitution of the carbonyls in these dicarbonylrhodium complexes by different tertiary phosphine ligands have also been identified using UV/Visible and IR spectroscopic techniques. One of the aims of this study was to determine the mechanism for the oxidative addition of [Rh(CH3cupf)(CO)(PX3)] ( X = Ph, p-MeOPh, p-Tol, o-Tol and Cy) with iodomethane and to investigate the effect of temperature and solvent, as well as the steric and electronic effect of the phosphine ligands on this reaction. The [Rh(CH3cupf)(CO)(PPh3)] complex is expected to have a similar geometric configuration as that of [Rh(cupf)(CO)(PX3)]. Extrapolation of this structural data predicted that the [Rh(CH3cupf)(CO)(PPh3)] complex also contain the CO group trans to the nitroso group. It can be concluded that the electronic properties of the cupferrate ligand overshadows the steric effect of the different phosphine ligands. The different Rh(I)-CH3cupf complexes underwent oxidative addition with iodomethane to form the corresponding Rh(III)-alkyl species followed by the slower formation of Rh(III)-acyl species according to the scheme below. All the Rh(I) and Rh(III) species were characterised by infrared spectroscopy. The rate constant for the oxidative addition of [Rh(CH3cupf)(CO)(PX3)] with iodomethane increased with increasing polarity of solvents. At 25.0 ºC, this reaction proceeds at a rate of k1 = 3.94(5) x 10-3 M-1s-1 in the highly polar methanol and at a rate of k1 = 1.33(4) x 10-3 M-1s-1 in less polar acetone, compared to the least polar benzene with a rate of k1 = 0.101(2) x 10-3 M-1s-1. Activation parameters (ΔH# and ΔS#) were determined for the temperature dependence of k1 in acetone. A large negative ΔS# value (ΔS# = -137(1) JK-1mol-1) and a positive ΔH# (ΔH# = 48(1) kJmol-1) were obtained which clearly point to an associative mechanism. Considering the experimental results, the formation of a linear, polar transition state with subsequent formation of an ion-pair intermediate is postulated for the intrinsic mechanism. The rate of formation of the Rh(III) acyl species was found to be independent of iodomethane concentrations. The rate constant of the oxidative addition was also affected by electronic and steric manipulations. The electronic effect was achieved by interchanging, for example, PPh3 with P(p-MeOC6H4)3 which resulted in a more than fivefold increase in magnitude for the rate of oxidative addition. An elevenfold decrease in the k1 value for P(o-Tol)3, when compared to P(p-MeOC6H4)3, showed the impact of the steric effect.

’n Aantal dikarbonielrodiumkomplekse, [Rh(CH3cupf)(CO)2], sowel as hulle gesubstitueerde monokarbonielprodukte [Rh(CH3cupf)- (CO)(PX3)] (waar X = Ph, p-MeOph, p-Tol, o-Tol en Cy) is berei en geïdentifiseer met behulp van IR and KMR tegnieke. Die vierkantig-planêre substitusie van die karboniele in hierdie dikarbonielrodiumkomplekse deur verskillende tersiêre fosfienligande is ook geïdentifiseer deur gebruikmaking van UV/Sigbare en IR spektroskopiese metodes. Een van die doelwitte van hierdie studie was om die meganisme van die oksidatiewe addisie van [Rh(CH3cupf)(CO)(PX3)] ( X = Ph, p-MeOPh, p-Tol, o-Tol and Cy) met jodometaan te bepaal en om die invloed van temperatuur en oplosmiddel, asook die steriese- en elektroniese effek van die fosfienligande op hierdie reaksie te ondersoek. Die [Rh(CH3cupf)(CO)(PPh3)] kompleks behoort dieselfde geometriese konfigurasie as [Rh(cupf)(CO)(PX3)] te hê. Ekstrapolering van hierdie struktuurdata lei tot die voorspelling dat die [Rh(CH3cupf)(CO)(PPh3)] kompleks ook die CO groep trans ten opsigte van die nitrosogroep bevat. Daar kan tot die slotsom gekom word dat die elektroniese eienskappe van die cupferraatligand die steriese effek van die fosfienligande ooskadu. Die verskillende Rh(I)-CH3cupf komplekse ondergaan oksidatiewe addisie met jodometaan om die ooreenstemmende Rh(III)- alkielspesies te vorm, gevolg deur die stadiger vorming van die Rh(III)-asielspesies volgens die skema hieronder. Al die Rh(I) en Rh(III) spesies is gekarakteriseer met behulp van infrarooi spektroskopie. Die tempokonstante vir die oksidatiewe addisie van [Rh(CH3cupf)(CO)(PX3)] met jodometaan neem toe met toenemende polariteit van die oplosmiddels. Hierdie reaksie verloop by 25.0 ºC in die hoogs polêre metanol om ’n tempokonstante van k1 = 3.94(5) x 10-3 M-1s-1 te lewer, met k1 = 1.33(4) x 10-3 M-1s-1 in die minder polêre asetoon en k1 = 0.101(2) x 10-3 M-1s-1 in die mins polêre benseen. Aktiveringsparameters (ΔH# and ΔS#) is bepaal vir die temperatuurafhanklikheid van k1 in asetoon. ’n Groot negatiewe ΔS# waarde (ΔS# = -137(1) JK-1mol-1) en positiewe ΔH# (ΔH# = 48(1) kJmol-1) is verkry wat op ’n assosiatiewe meganisme dui. Met inagneming van die eksperimentele resultate kan die vorming van ’n lineêre, polêre oorgangstoestand met die daaropvolgende vorming van ’n ioonpaar intermediêr as intrinsieke meganisme gepostuleer word. Die tempo van vorming van die Rh(III)- asielspesie is as onafhanklik van die jodometaan-konsentrasie bevind. Die tempokonstante van die oksidatiewe addisiereaksie was ook afhanklik van elektroniese en steriese manipulasies van die rodiumkomplekse. Die veranderinge in die elektroniese effek is verkry met fosfieligandwisseling, deur byvoorbeeld PPh3 met P(p- MeOC6H4)3 te vervang wat gelei het tot ’n vyfvoud toename in die tempo van oksidatiewe addisie. ’n Elfvoudige afname in die k1 waarde vir P(o-Tol)3 in vergelyking met P(p-MeOC6H4)3 toon die dramatiese uitwerking van die steriese effek van fosfienligande.
Dissertation (M.Sc. (Chemistry))--University of the Free State, 2005
Keywords: Rhodium compounds -- Synthesis; Ligands; Complex compounds